2017
DOI: 10.3758/s13414-016-1263-8
|View full text |Cite
|
Sign up to set email alerts
|

Object-location binding across a saccade: A retinotopic spatial congruency bias

Abstract: Despite frequent eye movements that rapidly shift the locations of objects on our retinas, our visual system creates a stable perception of the world. To do this, it must convert eye-centered (retinotopic) input to world-centered (spatiotopic) percepts. Moreover, for successful behavior we must also incorporate information about object features/identities during this updating – a fundamental challenge that remains to be understood. Here we adapted a recent behavioral paradigm, the “Spatial Congruency Bias”, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
97
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(121 citation statements)
references
References 96 publications
20
97
4
Order By: Relevance
“…One critical question is whether the Spatial Congruency Bias is a purely spatial effect reflecting low-level retinotopic input, or whether it is sensitive to more ecologically relevant information about an object's location. Recent studies from our group have found that the Spatial Congruency Bias remains in retinotopic (not spatiotopic) coordinates after a saccadic eye movement (Shafer-Skelton et al, 2017), and that the congruency bias is driven by 2D (not 3D) spatial location information (Finlayson & Golomb, 2016). However, it has long been known that one of the most compelling cues for object “sameness” is spatiotemporal contiguity (Burke, 1952; Flombaum et al, 2009; Hollingworth & Franconeri, 2009; Kahneman et al, 1992; Mitroff & Alvarez, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…One critical question is whether the Spatial Congruency Bias is a purely spatial effect reflecting low-level retinotopic input, or whether it is sensitive to more ecologically relevant information about an object's location. Recent studies from our group have found that the Spatial Congruency Bias remains in retinotopic (not spatiotopic) coordinates after a saccadic eye movement (Shafer-Skelton et al, 2017), and that the congruency bias is driven by 2D (not 3D) spatial location information (Finlayson & Golomb, 2016). However, it has long been known that one of the most compelling cues for object “sameness” is spatiotemporal contiguity (Burke, 1952; Flombaum et al, 2009; Hollingworth & Franconeri, 2009; Kahneman et al, 1992; Mitroff & Alvarez, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent paper, we tested an additional manipulation of the Spatial Congruency Bias – whether it was tied to absolute (spatiotopic) locations or eye-centered (retinotopic) locations following an eye movement (Shafer-Skelton et al, 2017). The Spatial Congruency Bias was linked purely to retinotopic location; even at longer delays after the saccade (more time to update) and for objects of varying complexity (gabors, objects, and faces), there was no evidence for spatiotopic binding (Shafer-Skelton et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations